CO-BRANDING AS A TOOL FOR FORMING JOINT INNOVATIVE MARKETING ACTIVITIES OF DAIRY PROCESSING ENTERPRISES - KARPENKO, Vitalii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the use of co-branding as a tool for forming joint innovative marketing activities of milk processing enterprises. Co-branding is defined as a marketing strategy where two or more businesses join together to jointly produce a product or service under a common brand. The main benefit of co-branding is that it can help increase brand awareness, attract new customers, increase sales and strengthen market positions. Co-branding marketing alliances are one of the most productive forms of cooperation between corporations, an integral part of the competition for customers and their loyalty. This line of activity will make it possible to obtain a synergistic effect by combining internal and external factors of reputational capital formation of corporations that will participate in co-branding projects.It has been established that an important direction of marketing strategic planning in the context of the development of co-branding is the development (diversification) of the product, which should be additionally offered to the strategic alliance taking into account the study of global trends in the field of healthy nutrition, that is, the expansion of the product range, namely the introduction of the production of lactose-free milk, because in the world, there is a significant increase in the population with the problem of assimilation of lactose, which is contained in the milk of cattle, which causes the search for innovative types of dairy products.
Keywords: branding; co-branding; trade mark; brand alliancesbrand alliances; brand networks; competition; loyalty